FIRST PACIFIC WHITE SHRIMP, LITOPENAEUS VANNAMEI (BOONE, 1931) CULTURE IN PAKISTAN: EVALUATION OF OPTIMUM SALINITY LEVEL FOR THE GROWTH PERFORMANCE AND SURVIVAL IN THE HYPO SALINE AND HYPER SALINE CONDITION UNDER POND ECOSYSTEM - Habib Ul Hassan; K. Gabol; J. Wattoo; A. M. Chatta; Q. M. Ali; K. Mahmood; M. Hussain; N.A.Abro; M. Attaullah; S. U. Rahman; A. Rashid; M. A. Rahman; et al. (Journal of Animal and Plant Sciences, 2021)
The present study was conducted in the coastal pond ecosystems of Pakistan to evaluate the optimum salinity level for the best growth performance of a commercial shrimp, Litopenaeus vannamei. Total of 6 lac seed was randomly distributed in three ponds with an average initial body weight of 0.1±0.01 g. The shrimps were cultivated in three different ponds demarcated as pond 1, pond 2 and pond 3 with salinity levels of 8 ppt, 22 ppt and 42 ppt, respectively for 105 days. The pacific white shrimpwere fed with 35.0% crude protein diet with feeding frequency of 4 and initially feeding rate of 10% biomass per day. The feeding rate adjusted according to shrimp biomass on a weekly basis. Final weight, specific growth rate, average daily weight gain, viscerosomatic index, hepatosomatic index and survival rates were found optimum at salinity level of 22 ppt compared with salinity levels of 8 ppt and 42 ppt (p <0.05). FCR was better at 22 ppt salinity compared with two other tested salinity levels (p <0.05). The 22 ppt salinity level resulted in optimum growth of L. vannamei which might be due to improved osmoregulation. Feeding frequency of 4, protein 35% and salinity of 22 ppt were found suitable factors for the growth performance of L. vannamei reared in aquaculture system.
Keywords: Litopenaeus vannamei; salinity; growth; survival rate; aquaculture